Public health partnerships: Does the evidence justify the enthusiasm?. Issue 2 (March 2015) - Graham, Ross; Sibbald, Shannon L.; Patel, Pooja
Partnerships are commonly identified as a foundational public health strategy. However, despite the prevalence and enthusiasm for partnerships, there are few published evaluations of public health partnerships in the Canadian context, and international literature reports that most partnerships have little to no effect on health outcomes. The contradicting enthusiasm and evidence create a challenging scenario for Canadian public health leaders and practitioners who are encouraged to both engage in partnerships and implement evidence-informed practices.